Case of early infant congenital bilateral axillary vein thrombosis discovered by superficial venous dilatation; a case report - Hiroki Ishii; Shinichiro Morichi; Yusuke Watanabe; Kanako Hayashi; Gaku Yamanaka (BMC Pediatrics)
Abstract Background Upper extremity deep venous thrombosis (UEDVT) is a disease caused by angiectopia and hypercoagulation,　which result in the superficial vein to become dilatated by the development of collateral circulation. There have been no reports to date of cases of bilateral axillary vein thrombosis developing in the early infant period. Moreover, whether anticoagulant administration is indicated varies among patients. Case presentation A 1-month-old boy presented with dilatated superficial veins in the right temporalis, right auricle, whole face, and bilateral upper limbs. Venous dilatation of the right temporalis worsened while crying. He had no notable family history. The patient’s heart had a normal structure, and the foramen ovale was patent on transthoracic echocardiography, and closed at 3-months old. Bilateral axillary vein thrombi were displayed on bilateral brachial vein angiography. Anticoagulants were not administered because the patient’s systemic circulation developed normally, and our analysis did not detect any abnormal coagulation disorders in the patient. However, the patient suddenly developed right hemiplegia at 6-months old, which naturally resolved without the administration of anticoagulants. Conclusion In patients presenting with bilateral UEDVT, the administration of anticoagulants should be considered owing to the possibility of vasculitis and congenital abnormal coagulation disorders.